Adjuvant denosumab in early breast cancer (D-CARE): an international, multicentre, randomised, controlled, phase 3 trial. Issue 1 (January 2020) - Coleman, Robert; Finkelstein, Dianne M; Barrios, Carlos; Martin, Miguel; Iwata, Hiroji; Hegg, Roberto; Glaspy, John; Periañez, Alvaro Montaño; Tonkin, Katia; Deleu, Ines; Sohn, Joohyuk; Crown, John; et al.
Summary: Background: Denosumab is a fully human monoclonal antibody that binds to, and inhibits, the receptor activator of RANKL (TNFSF11) and might affect breast cancer biology, as shown by preclinical evidence. We aimed to assess whether denosumab combined with standard-of-care adjuvant or neoadjuvant systemic therapy and locoregional treatments would increase bone metastasis-free survival in women with breast cancer. Method: In this international, double-blind, randomised, placebo-controlled, phase 3 study (D-CARE), patients were recruited from 389 centres in 39 countries. We enrolled women (aged ≥ 18 years) with histologically confirmed stage II or III breast cancer and an Eastern Cooperative Oncology Group performance status of 0 or 1. On eligibility confirmation, investigators at each site telephoned an interactive voice response system to centrally randomly assign patients (1:1) based on a fixed stratified permuted block randomisation list (block size 4) to receive either denosumab (120 mg) or matching placebo subcutaneously every 3–4 weeks, starting with neoadjuvant or adjuvant chemotherapy, for about 6 months and then every 12 weeks for a total duration of 5 years. Stratification factors were breast cancer therapy, lymph node status, hormone receptor and HER2 status, age, and geographical region. The primary endpoint was the composite endpoint of bone metastasis-free survival. This trial is registered with ClinicalTrials.gov, NCT01077154 . Findings: Between June 2, 2010, and Aug 24, 2012, 4509 women were randomly assigned to receive denosumab (n=2256) or placebo (n=2253) and included in the intention-to-treat analysis. The primary analysis of the study was done when all patients had the opportunity to complete 5 years of follow-up with an analysis data cutoff date of Aug 31, 2017. The primary endpoint of bone metastasis-free survival was not significantly different between the groups (median not reached in either group; hazard ratio 0·97, 95% CI 0·82–1·14; p=0·70). The most common grade 3 or worse treatment-emergent adverse events, reported in patients who had at least one dose of the investigational product (2241 patients with denosumab vs 2218 patients with placebo), were neutropenia (340 [15%] vs 328 [15%]), febrile neutropenia (112 [5%] vs 142 [6%]), and leucopenia (62 [3%] vs 61 [3%]). Positively adjudicated osteonecrosis of the jaw occurred in 122 (5%) of 2241 patients treated with denosumab versus four (<1%) of 2218 patients treated with placebo; treatment-emergent hypocalcaemia occurred in 152 (7%) versus 82 (4%). Two treatment-related deaths occurred in the placebo group due to acute myeloid leukaemia and depressed level of consciousness. Interpretation: Despite preclinical evidence suggesting RANKL inhibition might delay bone metastasis or disease recurrence in patients with early-stage breast cancer, in this study, denosumab did not improve disease-related outcomes for women with high-risk early breast cancer. Funding: Amgen.